Spatial differentiation of Stryi raion of Lviv oblast: challenges for development - Vlakh , Myroslava; Vanda , Iryna; Kotyk, Liubov (Human Geography Journal, 2022)
The article raises the issue of comprehensive human-geographical research of administrative-territorial units formed as a result of reforming the administrative-territorial structure of Ukraine. The human-geographical meaning of the concept of "administrative district capacity" as its ability to function effectively in accordance with natural, demographic and economic potentials is introduced and revealed. Using a cartographic method, a series of analytical maps elaborated, which revealed significant spatial heterogeneity in terms of territorial communities of Stryi Raion (district) in terms of providing by land resources, population and settlement density, level of urbanization, general budget revenues per unit area and per capita, taфability index.Based on the Methodology for the Formation of Capable Territorial Communities (2020), groups of territorial communities with high (3.9 – 4.6) and medium (3.2 – 3.8) levels of capacity identified at the studied area. Elaboration of the approved strategies for the development of territorial communities made it possible to summarize the priority areas of economic development of the district: tourism and recreational, transport and logistical, agrarian, industrial. Clustering is proposed as an effective process of territorial organization of the economy of Stryi Raion. The need to transform the city-forming functions of the former district centers (Zhydachiv, Mykolaiv, Skole) into new economic realities is emphasized.